Acyl Phosphates from Low Oxidation State Phosphorus for the Synthesis of Amides, Ketones and Heterocycles - Green, Michael T. (2022)
Chapter I described the use of diethyl phosphite to activate carboxylic acids via acyl phosphate formation, using an aerobic copper-catalysed system. The acyl phosphates were used to synthesise a variety of amides in good yields (35-78 %), using 10 mol % catalyst. Simple methods of purification such as precipitating the amide from the reaction mixture produced amides in high purity. Initial insight into a potential mechanism suggests the reaction proceeds via the copper (II) oxidation state and that the halide counter anion can participate in the reaction.